DETERMINAN KECENDERUNGAN KECURANGAN PADA PENGELOLAAN DANA DESA DENGAN SISTEM PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI DI KECAMATAN LANGSA LAMA - Puteri, Makhfirah; Afrah Junita; Agustina Nurul Fajriah (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This research aims to determine the influence of Self Interest, bystander effect, organizational culture on the tendency to cheat in village fund management with the internal control system as a moderating variable. This type of research uses quantitative research, the data source for this research uses primary data. The population and sample for this research are villages in Langsa Lama District, totaling 15 villages as the population and the samples taken in this research were 75 samples. This research uses purposive sampling, namely a certain sampling technique based on certain considerations or criteria. The data obtained was analyzed using the PLS (Partial Least Square) analysis technique. The equation models analyzed are outer model, inner model and hypothesis testing. The results obtained from this research are: (1) Self interest has a negative effect on the tendency to cheat, (2) Bystander effect has no effect on the tendency to cheat, (3) Organizational culture has no effect on the tendency to cheat, (4) The internal control system has no effect on tendency to cheat, (5) The internal control system is not able to moderate the relationship between self-interest and the tendency to cheat in the management of village funds, (6) The internal control system is not able to moderate the bystander effect relationship to the tendency to cheat in the management of village funds, (7) The internal control system is not able to moderate the relationship between organizational culture and the tendency for fraud in village fund management.